Association between depression and functional dependence in elderly patients - Runzer-Colmenares, Fernando M. (2017)
Objective: To determine the association between depression and functional dependence in elderly patients of the Centro Geriátrico Naval (Peruvian naval medical center for elderly people). Materials and methods: A retrospective, cross-sectional, analytic study conducted from a secondary data analysis, with a convenience sample size of 625 elderly people. Results: In the linear regression analysis which predicts functional dependence according to the Barthel Index, it was found that, for each point in the Yesavage questionnaire, the Barthel Index score decreases 4.8±1.82 points and, for every 5 points, it decreases 29.99±3.62 points. In relation to the Lawton Index, significant outcomes were found regarding age, gender, military rank, physical performance, grip strength and depression. Conclusions: The results show an association between depression and functional dependence in performing basic and instrumental activities of daily life. Moreover, the higher the risk of depression, the higher the chance of developing functional dependence according to the Barthel Index, regardless of other variables.